2022
DOI: 10.1007/s00395-022-00947-2
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic conditioning: defining critical criteria for success—report from the 11th Hatter Cardiovascular Workshop

Abstract: The Hatter Cardiovascular Institute biennial workshop, originally scheduled for April 2020 but postponed for 2 years due to the Covid pandemic, was organised to debate and discuss the future of Remote Ischaemic Conditioning (RIC). This evolved from the large multicentre CONDI-2–ERIC–PPCI outcome study which demonstrated no additional benefit when using RIC in the setting of ST-elevation myocardial infarction (STEMI). The workshop discussed how conditioning has led to a significant and fundamental understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…Therefore, enrolling participants in different phases of their disease may in part explain our findings. While the aforementioned limitations may not have fully unmasked a positive signal from RIC, our study has been very helpful in identifying and validating potential pitfalls for success as described by Bell et al [ 19 ] and highlights the need to further investigate the easily accessible and cost-effective benefits of RIC in patients with COVID-19. Given the involvement of ongoing inflammation with possible cytokine elevation in patients with long COVID-19 and the paucity of specific treatments for this syndrome, it may be interesting to study the potential benefit of RIC in this population [ 43.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, enrolling participants in different phases of their disease may in part explain our findings. While the aforementioned limitations may not have fully unmasked a positive signal from RIC, our study has been very helpful in identifying and validating potential pitfalls for success as described by Bell et al [ 19 ] and highlights the need to further investigate the easily accessible and cost-effective benefits of RIC in patients with COVID-19. Given the involvement of ongoing inflammation with possible cytokine elevation in patients with long COVID-19 and the paucity of specific treatments for this syndrome, it may be interesting to study the potential benefit of RIC in this population [ 43.…”
Section: Discussionmentioning
confidence: 77%
“…Early repetitive or chronic RIC administration has shown benefits in reducing levels of inflammatory cytokines (such as TNF-α, IL-1β, and IL-6) following lipopolysaccharide-induced sepsis and has been associated with a reduction in mortality in mice [17]. In recent years, RIC has grown from being an innovative strategy for cardiovascular protection [19][20][21]. This emerging field of RIC has been thought to protect organs (e.g., brain, heart, lungs, and kidneys) against the harmful effect of ischemic/reperfusion injury through activation of cell survival pathways and modulation of inflammatory responses that improve mitochondrial function [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As for cardioprotective strategies, experimental studies in the early years from 2007 to 2012 had revealed the essential signal transduction pathways underlying local ischemic postconditioning and remote ischemic preconditioning [ 34 ]. For example, oxidative stress after ischemia/reperfusion produces a large number of reactive oxygen and nitrogen species, leading to cardiac cell death and contractile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to both, cardiomyocytes, i.e., infarct size [ 82 ], and the coronary microcirculation, i.e., microvascular obstruction [ 11 ], contribute to patients’ prognosis. Whereas encouraging preclinical and clinical proof-of-concept studies demonstrated reduced infarct size by mechanical and pharmacological cardioprotection strategies [ 27 ], their translation to better clinical outcome in phase III trials in patients with acute myocardial infarction has been largely disappointing [ 1 , 4 , 25 ]. Such failure of translation has primarily been attributed to co-morbidities and co-medications of patients with acute myocardial infarction which may impair cardioprotective signalling [ 26 ].…”
Section: Introductionmentioning
confidence: 99%